The Softskill and Hardskill forms of Tunjuk Ajar Melayu in Nyanyi Panjang Bujang Si Undang Palalawan Society of Riau Province - Erni Erni; Ridha Hasnul Ulya (STAI Hubbulwathan Duri, 2021)
This research is based on issues of tunjuk ajar inheritance that is no longer exists. The purpose of this study is to reveal and explain the points of tunjuk ajar Melayu Riau. This research is a content analysis research using qualitative descriptive methods. The method in analyzing the data in this research is carried out through three activities, namely: (1) data reduction, (2) data display, and (3) concluding. The results of this study are 4, namely: (1) teaching value related with the faith and piety in Nyanyi Panjang Bujang si Undang can be seen from the indicators of the behaviour of believing in God, doing the commands and leaving God's prohibitions, trustworthiness, sincerity, shame, low heart, and obedience to mother and father; (2) Tunjuk ajar in Nyanyi Panjang Bujang si Undang is reflected in the behaviour of saying as what it is, acting based on truth, and being responsible; (3) the intelligence character found in Nyanyi Panjang Bujang si Undang includes behavioural indicators, such as: directed, logical, and analytical thinking, being able to find solutions, careful, far-sighted, and the priority to study; and (4) nationality values in tunjuk ajar include behavioural indicators relating to unity and integrity, cooperation, rights and property, consensus agreement, and obedience to leaders.